Ответы и объяснения

2012-12-19T13:11:18+04:00

1)3sin^2 x+sin x*cos x-2cos^2 x=0|:cos^2 x

   3sin^2 x/cos^2 x + sin x*cos x/cos^2x - 2cos^2 x/cos^2 x

   3tg^2 x +tg x-2=0

   Замена:tg x=t

   3t^2+t-2=0

   D=1+24=25=5^2

   t1=-1+5/6=4/6=2/3

   t2=-1-5/6=-6/6=-1

  Вернемся к исходной переменной:

  а)tg x=2/3

     x=arctg 2/3+Пn,n принадлежит Z

 б)tg x=-1

    x=arctg (-1)+Пn,n принадлежит Z

    x=-arctg 1+Пn,n принадлежит Z

    x=-П/4+Пn,n принадлежит Z

Ответ:arctg 2/3+Пn,n принадлежит Z;-П/4+Пn,n принадлежит Z

 2)sin^2 x+sin x*cos x-2cos^2 x=0|:cos^2 x

     sin^2 x/cos^2 x+sin x*cos x/cos^2 x-2cos^2 x/cos^2 x=0

     tg^2 x+tg x-2=0

   Замена:tg x=t

   t^2+t-2=0

   D=1+8=9=3^2

   t1=-1+3/2=2/2=1

   t2=-1-3/2=-4/2=-2

 Вернемся к исходной переменной:

  а)tg x=1

     x=arctg 1+Пn,n принадлежит Z

    x=П/4+Пn,n принадлежит Z

   б)tg x=-2

      x=arctg (-2)+Пn,n принадлежит Z

     x=-arctg 2+Пn,n принадлежит Z

 Ответ:П/4+Пn,n принадлежит Z;-arctg 2+Пn,n принадлежит Z